“Mal de cintura” disorder characterization of pineapple MD2 in agroclimatic conditions of flat area of Valle del Cauca, Colombia - Gómez, Yesicamila; Ríos-Rojas, Liliana (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2020)
In some localities in Colombia a physiological disorder called "Mal de cintura", is present in MD2 pineapple productive farms. It is a deformation of the fruit due to the incomplete development of contiguous flowers that produces a physical damage (external appearance); generating fruit rejection in the market. Factors that trigger this problem are unknown. This research was carried out on two farms in Valle del Cauca, Colombia, soil moisture and ambient temperature conditions were evaluated on the expression of the physiological disorder. In farm 1, vegetative and productive phases of the crop were evaluated. The results indicate that the plants were not in water deficit before, during or after flowering, ruling out this factor on the expression of the physiological disorder. During flowering, maximum temperatures reached 35°C and minimum temperatures 18°C were recorded, giving an alert on this variable due to the presence of the physiological disorder of 96% of the crop. In farm 2, a more detailed monitoring of the temperatures was carried out during the inflorescence development. In this period, maximum temperature inside crop was 58,5°C and the minimum was 15,5°C, symptoms of deformation were present in 78% of the crop. Results were inconclusive about temperature influence on fruit deformation. A chemical analysis of inflorescences tissue with and without expression of the physiological disorder was performed to validate the influence of a nutritional problem. Results indicated that damaged inflorescences had higher copper, zinc and manganese contents than healthy inflorescences.